Tendencies of the Development of General Education School Heads’ and Teachers’ Leadership - Gumuliauskienė, Aušrinė; Vaičiūnienė, Asta (Social Welfare: Interdisciplinary Approach, 2018)
The article deals with the problems of the development of school heads’ and teachers’ leadership: the relevance of the development of leadership for systemic qualitative changes of school activity has been emphasized, referring to the results of the research the opportunities and conditions of the development of teachers’ leadership in school have been described, the relations of the development of leadership with the changes in school governance and culture have been substantiated, the tendencies of five years of the development of leadership in school have been revealed.